Welding and lung cancer in Central and Eastern Europe and the United Kingdom - 't Mannetje, Andrea; Brennan, Paul; Zaridze, David; Szeszenia-Dabrowska, Neonila; Rudnai, Peter; Lissowska, Jolanta; Fabiánová, Eleonóra; Cassidy, Adrian; Mates, Dana; Bencko, Vladimir; Foretova, Lenka; Janout, Vladimir; et al. (American journal of epidemiology, 2012)
Occupation as a welder has been associated with a 25%-40% increase in lung cancer risk. This study aims to elucidate to what extent confounding by smoking and asbestos drives this association and to evaluate the role of welding-related exposures such as chromium. The study included 2,197 male incident lung cancer cases and 2,295 controls from Romania, Hungary, Poland, Russia, Slovakia, the Czech Republic, and the United Kingdom from 1998 to 2001. Information on risk factors was collected through face-to-face interviews. Experts assessed exposure to 70 agents, and risk estimates were adjusted for smoking and occupational exposures. Occupation as a welder/flame cutter (prevalence controls: 3.7%) was associated with an odds ratio of 1.36 (95% confidence interval (CI): 1.00, 1.86) after adjustment for smoking and occupational exposures including asbestos. An odds ratio of 1.18 (95% CI: 1.01, 1.38) was found for welding fumes (prevalence controls: 22.8%), increasing to 1.38 for more than 25 exposure years (95% CI: 1.09, 1.75). A duration-response association was also observed for mild steel welding without chromium exposure. In this population, occupational exposure to welding fumes accounted for approximately 4% of lung cancer cases, to which both stainless and mild steel welding contributed equally. Given that welding remains a common task for many workers, exposure to welding fumes represents an important risk factor for lung cancer.
Keywords: Russia; Male; Slovakia; nádory plic; Slovenská republika; Occupational Exposure; odds ratio; Occupational Diseases; Welding; United Kingdom; Lung Neoplasms; Poland; Česká republika; nemoci z povolání; pracovní expozice; Adult; prevalence; Age Factors; Aged; dospělí; Case-Control Studies; mužské pohlaví; senioři; Rumunsko; Smoking; Czech Republic; Maďarsko; lidé; ženské pohlaví; studie případů a kontrol; Humans; Spojené království; Prevalence; věkové faktory; Rusko; Hungary; Odds Ratio; svařování; Female; Polsko; lidé středního věku; kouření; Romania; Middle Aged